The trouble with VAK - John Sharp; Jenny Byrne; Rob Bowker (Educational Futures)
Learning styles is arguably the most talked about phenomenon in schools at the present time. Here, we explore learning styles popularised as VAK and begin to interrogate some of the more unusual claims used to lend support to its credibility. Concerns are raised over the apparent rush to adopt VAK in an evidence-based profession which prides itself on critical reflection and analysis.